Where I End - White, Sophie (Journalist) (New York : Erewhon Books, Kensington Publishing Corp., 2024)
"My Mother. At night my mother creaks, the house creaks along with her. Sometimes in the morning we find her in places. We never see her move. We just come upon her. Aoileann is cursed. She has no friends, never gone to school. She has never left the windswept craggy isle off the coast of Ireland. Her mother is cursed: a silent wreck Aoileann calls the 'bed-thing'"--
Keywords: Women -- Fiction; Recluses -- Fiction; Social isolation -- Fiction; Mothers and daughters -- Fiction; Motherhood -- Fiction; Artists -- Fiction; Gothic fiction; Horror fiction